Evacuation System as a Route Guide on Signage at Jakarta International Stadium - Pawitra Sari; Desta Promesetiyo Bomo (DPPM Universitas Pelita Bangsa, 2023)
Stadiums with large capacity and high-rise buildings must be supported by architecture and information systems that can be presented in the form of signage. This study aims to describe the meaning of signage so that the path of movement has a sequence of evacuation routes in a fast, precise, and safe direction. Environment Graphics Design (EGD) is a solution for signage as a route guide for football spectators when disasters and emergencies occur. The analysis carried out is an evaluation of data and fact findings with literature on EGD theory, then conclusions are drawn. The evacuation system on signage, namely evacuation maps, exit signs, and assembly point signs, has a signage category as regulatory. The regulation follows the standard concerning Building Amenity Requirements and refers to OSH signage. Evacuation maps have signage categories as identification and directional, exit signs have signage categories as directional and warning, and assembly point signs have signage categories as identification and warning. The dominant visual and placement on signage are the exit signs, while the placement on the assembly point signs refers to the regulations as a refuge area. There are no evacuation maps around the emergency exit so football spectators who are not familiar with the stadium.